Factors associated with delays in the search for care in under-5 deaths in Yucatán, Mexico - Bernardo Hernández-Prado; Elsa María Rodríguez-Angulo; Erin B Palmisano; Ricardo Ojeda-Rodríguez; Rafael Javier Ojeda-Baranda; María Guadalupe Andueza-Pecha; Louisa M Johnson; Alan Chen; Casey Johanns; Neal Marquez; Aruna M Kamath; Joseph N Camarda; et al. (Instituto Nacional de Salud Pública, 2021)
Objective. We examined delays during the search for care and associations with mother, child, or health services characteristics, and with symptoms reported prior to death. Materials and methods. Cross-sectional study comprising household interviews with 252 caregivers of children under-5 who died in the state of Yucatán, Mexico, during 2015-2016. We evaluated the three main delays: 1) time to identify symptoms and start search for care, 2) transport time to health facility, and 3) wait time at health facility. Results. Children faced important delays including a mean time to start the search for care of 4.1 days. The mean transport time to the first facility was longer for children enrolled in Seguro Popular and there were longer wait times at public facilities, especially among children who also experienced longer travel time. Conclusions. Providing resources to enable caregivers to access health services in a timely manner may reduce delays in seeking care.